Omission of axillary dissection according to ACOSOG Z0011: impact on adjuvant treatment recommendations - Aigner, Julia; Smetanay, Katharina; Hof, Holger; Sinn, Peter; Sohn, Christof; Schneeweiss, Andreas; Marmé, Frederik (Annals of surgical oncology, 2013)
A recent, randomized trial (ACOSOG Z0011) has demonstrated that omission of completion axillary lymph node dissection (ALND) in patients with one or two sentinel lymph node (SLN) metastases treated with breast conserving therapy (BCT) does not have a negative impact on survival. This study evaluates the impact of omitting ALND on adjuvant treatment recommendations.
Gesehen am 07.05.2021